Needlestick and Sharps Injuries Among Operating Room Nurses, Reasons and Precautions - Dağcı, Mahmut; DAĞCI, MAHMUT; Sayın, Yazile; SAYIN, YAZİLE (My University, 2021)
Objective:Thisstudywascarriedouttodeterminetheneedlestickinjuries(NSI)oftheoperatingroomnurseswithpenetratingandsharptools,thecausesoftheinjuryandtheprecautionstakentopreventtheinjury.Methods:Adescriptiveandcross-sectionalstudywasconductedwiththeparticipationof463volunteernursesfrom27differenthospitalsinIstanbul,Turkey.Afterobtainingtheethicscommittee,institutionsandvolunteerpermissionsofthestudy,thedatawerecollectedwithtwodatacollectionformsformedinlinewiththeliteratureknowledgeandexpertopinions.ThedatawereanalyzedusingIBMSPSS22.0programandp<0.05wassignificancevalue.Results:Participantswere18-61yearsold,(mean:35.9±0.84),63.7%hadbachelor-sdegreesandabove,80.8%ofoperatingroomnursesweregraduatedfromnursingprogram.68.9%oftheparticipantsreportedthattheyhadlivedatleastonceduringtheirworkinglife.ThereweresignificantlydifferentforNSI(p<0.05)women,marriedandhadloweducationallevels,workinginuniversityhospitalswithdeepinvasiveinterventionandusingprotectiveequipment.Participantsreportedthat54.8%oftheinjurieswereperformedintherighthandandtheprimarycausewasexchanginginstrumentsbetweennurseandsurgeon,thesecondarywasassistingsurgeon.Mostoftheparticipants(37.1%)wereinjuredbythesuturematerial.ThemostcommonNSIencounteredoperatingtheaterswerepediatricsurgery,cardiovascularsurgery,thoracicsurgeryandgeneralsurgery.